A Genetic Algorithm Approach for Optimal Allocation and Sizing of Distributed Generation in Distribution Networks - Panjiyar, Anil Kumar; Jha, Abhinav; Yadav, Rashmi (Journal of Advanced College of Engineering and Management, 2026)
Numerous advantages attained by integrating Distributed Generation (DG) in distribution systems. These advantages include decreasing power losses and improving voltage profiles. Such benefits can be achieved and enhanced if DGs are optimally sized and located in the systems. This study presents a distributed generation (DG) allocation strategy to improve node voltage and power loss of radial distribution systems using genetic algorithm (GA). The objective is to minimize active power losses while keep the voltage profiles in the network within specified limit. In this study, the optimal DG placement and sizing problem is investigated using two approaches. First, the optimization problem is treated as single-objective optimization problem, where the system’s active power losses are considered as the objective to be minimized. Secondly, the problem is tackled as a multi-objective one, focusing on total power loss as well as voltage profile of the networks. This approach finds optimal DG active power and optimal OLTC position for tap changing transformer. The simulation study is carried out on a 33-bus radial Distribution System. The results are presented, compared and analyzed in this paper.